Synthesis, characterization, preliminary molecular docking, pharmacological activity, and ADME studies of some new pyrazoline derivatives as anti-breast cancer agents - Hayder R. Fadhil; Ayad M. R. Raauf; Monther F. Mahdi (Pensoft Publishers, 2024)
This work studied the anti-breast cancer activities of pyrazoline-containing benzenesulfonamides (6-10) in vitro and silico. The GOLD suite performed molecular docking on the target human estrogen receptor and the PARPA1 antagonist crystal structure, yielding comparable results using tamoxifen as a reference drug. Researchers tested these compounds (6-10) on two types of breast cancer cells (MCF-7 and MDA-MB-468) in the lab and found an antiproliferative activity that depended on the dose. Compounds 9 demonstrated a high docking score on PARP1 antagonist crystal structure in triple-negative breast cancer with a PLP fitness score of 93.24 and potential antiproliferative activity with an IC50 of 2.79 µM on the MDA-MB-468 cell line. In contrast, compounds 8 and 10 showed promising activity on the MCF-7 cancer cell line with IC50s of 7.4 and 17.96, respectively.